Overview of Information Literacy Proficiency among First Year Students of Biology Education Study Program in Universitas Tidar - Ika Sukmawati; Setiyo Prajoko; Ericka Darmawan (Universitas Tidar, 2018)
Developments in all fields demand changes in learning, including at university level. Various skills for successful life in the future must be trained in students, including information literacy. This study aims to get an overview of students’ information literacy proficiency based on their experience during high school, the main source of information ever used, and the students’ perception of information literacy capacity. This study used a survey method, with an information literacy questionnaire distributed to 89 first-year students of the Biology Education Study Program, Universitas Tidar. The collected data were analyzed descriptively. Based on the results of the study it was found that students already had the experience of accessing information for completing assignments during high school. Information obtained by students is mainly obtained from Google and books. However, the use of Google as a search engine has not been directed towards finding quality sources. Students are still have low capacity in information literacy skills, especially those relating to the use of information effectively and ethically. The results of this study are expected to be the basis for establishing information literacy training programs in Biology Education Study Program Universitas Tidar, both integrated in the subjects and on their own.